Adaptive Fault-Tolerate Lateral Control for Autonomous Electric Vehicles with Unknown Parameters and Actuator Faults. (13th April 2023) - Liu, Haiyan; Wang, Yadong; Wang, Kunfeng
Abstract : In this paper, the fault-tolerant lateral control problem is considered for autonomous electric vehicles with unknown parameters and actuator faults. In the real world, the physical characteristics of vehicles are time-varying, causing that the parameters are unknown and even piecewise. Besides, the actuators may encounter with intermittent actuator faults, which can destroy the system's performance. To deal with the piecewise unknown parameters and actuator faults, quadratic damping terms are designed in the controller and estimators are introduced to estimate those uncertainties. Then, by utilizing the backstepping technique, a novel adaptive fault-tolerant lateral control scheme is proposed, which guarantees that the tracking errors converge into a compact set. Simulation results are provided to validate the effectiveness and robustness of the proposed control scheme.